CHA2DS2-VASC score predicts coronary artery disease progression and mortality after ventricular arrhythmia in patients with implantable cardioverter-defibrillator. (June 2021) - Kavsur, Refik; Becher, Marc Ulrich; Nassan, Welat; Sedaghat, Alexander; Aksoy, Adem; Schrickel, Jan Wilko; Nickenig, Georg; Tiyerili, Vedat
Abstract: Aim: The CHA2 DS2 -VASC score has expanded its use beyond the initial purpose of predicting the risk of stroke in patients with atrial fibrillation. We aimed to investigate the value of the CHA2 DS2 -VASC score as a risk assessment tool to predict relevant coronary artery disease (CAD) leading to percutaneous coronary intervention (PCI), and all-cause mortality after detected ventricular arrhythmia (VA) in patients with an Implantable Cardioverter-Defibrillator (ICD). Methods: A total of 183 ICD-patients who underwent coronary angiography after VA were included and classified according to their CHA2 DS2 -VASC score in a low(1-3), intermediate(4-5) and high(6-8) score group. We evaluated the predictive value of CHA2 DS2 -VASC score for the presence of relevant CAD leading to percutaneous coronary intervention (PCI), as well as late all-cause mortality. Results: A total of 60 patients (32.8%) had significant CAD and underwent successful PCI. After adjustment for relevant parameters such as ischemic cardiomyopathy, angina pectoris, left ventricular ejection fraction, CHA2 DS2 -VASC score remained the only independent predictor of CAD leading to PCI [HR 1.73 (1.07–2.80)]. The Area under curve was 0.64 (0.56–72, p = 0.002). Kaplan-Meier analysis and log-rank showed an increased three-year mortality of ICD-patients with an intermediate or high score after VA (p = 0.003). Multivariate cox-regression analysis revealed that CHA2 DS2 -VASC score was also independently associated with all-cause mortality following adjustment for clinically relevant variables (HR 2.20, 1.17–4.14). Conclusions: CHA2 DS2 -VASC score can be a predictor of CAD leading to PCI in ICD-patients after VA. ICD-Patients with a high score have an increased risk for reduced three-year all-cause mortality after VA.